Predicting Factors of Mammography Adherence among Iranian Women Based on Transtheoretical Model - mahsa khodayarian; Tahmineh farajkhoda; Azita Aryaeenezhad; Mozhgan Sharifi (Golestan University of Medical Sciences, 2020)
Background: Breast cancer is the most common cancer among women in Iran. Early diagnosis of breast cancer by mammography could decrease the rate of mortality and improve the survival rate. This study aimed to determine the predicting factors of mammography adherence among Iranian women based on transtheoretical model. Methods: This cross-sectional study was done on 300 married women in Yazd in 2018. Subjects was recruited using cluster sampling. Data were gathered through researcher-made questionnaire based on trans-theoretical model. The constructs of decisional balance, self-efficacy, stages and process of change were studied. Data were analyzed using chi-square test, one-way analysis of variance, Spearman correlation coefficient and regression analysis in SPSS-16 software.  Results: The mean age of women was 47.25±6.97 years old (ranged from 40 to 70). Most of the participants (86.4%) were in inactive stages of decision-making for performing mammography and only 5.3% were in active stages. The mean score of self-efficacy among the studied women was 24.54±6.5. According to linear regression test, the validity of the predicting trans-theoretical model by all of its constructs together was 47%. Conclusions: Results of the present study showed that most of the women were at inactive stages of decision-making for mammography behavior and, based on the results, to improve the stages of the behavior, their self-efficacy should be improved.